The Elderly and the Determinants of Stress - Fayola Issalillah; Nur Aisyah (Journal of Social Science Studies (JOS3), 2022)
The adult phase or the productive phase of a person is spent with various activities both for work or socializing with friends or friends. Generally, someone will prepare for retirement only in the financial sector, not in other social aspects. Many of the elderly feel unappreciated and lonely. Situations like this will usually cause stress in the elderly. As a result of stress in general, if it cannot be overcome by the elderly, it can cause the elderly to experience physical decline. Therefore, this study was conducted to determine the source of stress in the elderly. This research is descriptive qualitative research because this research presents descriptive data about the factors that cause stress in the elderly. From research conducted, the elderly experience stress due to changes in the way of life they go through. Many routines with excellent physical conditions are a dream for the elderly. Some of the elderly who do not have financial stability still have to carry out their routine activities without being supported by good physical conditions.